2017
DOI: 10.2807/1560-7917.es.2017.22.4.30450
|View full text |Cite
|
Sign up to set email alerts
|

Live attenuated influenza vaccine effectiveness against hospitalisation due to laboratory-confirmed influenza in children two to six years of age in England in the 2015/16 season

Abstract: The United Kingdom is introducing a universal annual influenza vaccination programme for children. Live attenuated influenza vaccine (LAIV) effectiveness (VE) against laboratory-confirmed influenza hospitalisation in 2 to 6 year-olds in England was measured in 2015/16 using the screening method. VE adjusted for age, geography and month was 54.5% (95% confidence interval (CI): 31.5% to 68.4%) for all influenza types combined; 48.3% (95% CI: 16.9% to 67.8%) for A(H1N1)pdm09 and 70.6% (95% CI: 33.2% to 87.1%) for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 10 publications
(18 reference statements)
3
23
0
1
Order By: Relevance
“…PPV were then matched to each varicella cases based on their year of survey/notification, age, and number of dose(s) received. We computed the VE following the approach suggested by Farrington, 15 which was also adopted and described in detail in other VE studies: 12,16,17 In…”
Section: Estimation Of Vementioning
confidence: 99%
“…PPV were then matched to each varicella cases based on their year of survey/notification, age, and number of dose(s) received. We computed the VE following the approach suggested by Farrington, 15 which was also adopted and described in detail in other VE studies: 12,16,17 In…”
Section: Estimation Of Vementioning
confidence: 99%
“…In the United Kingdom, annual single-dose LAIV given to children aged 2-16 years since 2013 has significantly reduced severe influenza disease. 6 Pre-licensure and early post-marketing surveillance data showed that LAIV-protection was comparable to inactivated vaccines. 7 Animal models of influenza infection demonstrate increased density and duration of pneumococcal carriage.…”
Section: Introductionmentioning
confidence: 99%
“…In 2014-15, LAIV was effective against B/Yamagata, but not A/H3N2 (41,42). This pattern remained during the 2015-16 season, with low VE against A/ H1N1pdm09 and A/H3N2 strains, but overall effectiveness against B viruses (44,45,47).…”
Section: Review Of Post-licensure Experience: From Early Success To Rmentioning
confidence: 92%
“…These conflicting data have introduced several significant questions and interpretations. The loss of LAIV effectiveness appears to be largely specific to the United States, with sustained VE in Germany, Canada, the United Kingdom, and Finland (36,40,44,45). This suggests that certain vaccination or production strategies particular to the United States could contribute to decreased effectiveness.…”
Section: Conundrums: Disparity Among Laiv Effectiveness Studiesmentioning
confidence: 99%